Regulating Conflict in Public Sector Labour Relations: The Ontario Experience (1984–1993) - Hebdon, Robert; Mazerolle, Maurice (Relations industrielles / Industrial Relations, 2003)
AbstractUsing a comprehensive collective bargaining data set, we examine dispute resolution patterns of all bargaining units in the province of Ontario over a 10-year period. A central finding is that bargaining units covered by legislation requiring compulsory interest arbitration arrive at impasse 8.7 percent to 21.7 percent more often than bargaining units in the right to strike sectors. Even after controlling for legislative jurisdiction, union, bargaining unit size, occupation, agreement length, time trend, and part-time status, strong evidence was found that compulsory arbitration has both chilling and dependence effects on the bargaining process. The problem of failure to reach negotiated settlements is particularly acute in the health care sector, especially among hospitals. Our results also call into question the use of interest arbitration in a central bargaining context. The centralized structure appears to exacerbate the negative effects of interest arbitration.